THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1943)
According to an old adage, competition is the life of trade. Exchange of ideas provides a surplus to improvement of educational processes. It is hoped that material dealing with the broader aspects of accounting education may be forthcoming for use in this department. Opinions might be exchanged on a variety of matters in connection with educational policy, curriculum alterations, course content, and the like. There are very few people who would favor a highly specialized education in accountancy to the exclusion of all general subjects. In some cases necessity rather than choice produces that unfortunate result. Public accountants, as customers of the colleges supplying graduates, are mud like other customers. They know what they like. They are not sure just why they hesitate to make suggestions for improvement. Manufacturers often try to learn to serve better by stirring customers to analyze the basis of their choices. Accounting teachers could do likewise. One of the advantages of work in a foreign language is the enforced contact with the mechanics of language structure. In addition, in many courses frequent papers and reports are expected which give further practice in the use of language.